The Construction of Diversified Funding Mechanism of Chinese Rural Power: A Grid Upgrading Project Based on the Practice of Rural Power Grids Upgrading in China - Chao, Kong (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
During the twelfth Five-Year plan of China, in order to solve many problems that exist in the rural power grids and change the situation that some rural areas lack the supply of electric power, the Chinese government proposed a new round of rural power grid upgrading project. Rural power grid upgrading project need a large mount of funding.The current funding mechanism of rural power grid upgrading project China is single,and it can not fully meet the demand for funds of rural power grid upgrading project. Therefore, based on the current situation of Chinese market-oriented reforms and the rapid development of social organizations,making the design of diversified funding mechanism of chinese rural power grid upgrading project.By utilize of fiscal funds , private capital, social capital and financial capital to build the diversified funding mechanism of chinese rural power grid upgrading project, it will meet the demand for funds of rural power grid upgrading project.